Strategi Umpan Balik Sebagai Alternatif Strategi Pembelajaran - Dila Oktaviani; Gusmaneli Gusmaneli (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Learning Islamic Religious Education (PAI) for some students is so unpleasant that it affects their interest in learning. One of the factors is that PAI learning strategies are still traditional, PAI teachers' teaching abilities/competence are still lacking, and PAI learning management strategies are not optimal. Efforts to increase PAI learning activities, PAI learning achievement, and make PAI a subject that students are interested in, the alternative is to change PAI learning strategies from traditional to progressive PAI learning strategies.